Endodontists perceptions of single and multiple visit root canal treatment: a survey in Florianópolis – Brazil - Monica de Souza Netto; Flavia Saavedra; Jacy Simi Júnior; Ricardo Machado; Emmanuel João Nogueira Leal Silva; Luiz Pascoal Vansan (Revista Sul-Brasileira de Odontologia, 2015)
One of the main debates that have occurred in Endodontics is about the amount of sessions required to complete an appropriate treatment. There are very different philosophies regarding this matter. Objective: to the aim of this study was to investigate the Endodontists’ point of view regarding single and multiple visit root canal treatment, identifying the basis on which the choice is made and how the information necessary for the choice is acquired. Material and methods: Endodontists registered in the dental practice board of Florianópolis/SC were contacted, and if they agreed to participate, they were interviewed using a questionnaire. The following topics were addressed: demographics, current clinical procedures, treatment rationales and preferences. Forty-three endodontists agreed to participate in the study. Results: Single visit endodontic treatment is carried out in 59.5% of biopulpectomy cases, 31.0% of necropulpectomy cases without lesion and only 11.9% in necropulpectomy cases with periapical lesion. The presence of vital pulp (81.4%) and a canal without exudate (93.0%) are the most important criteria for carrying out single visit endodontic treatment. The most used intracanal medication was calcium hydroxide. The lack of studies comparing long-term success on single visit endodontic treatment is considered an important issue to determine this therapy. Conclusion: It can be concluded that Florianopolis-Brazil endodontists prefer multiple visit over single visit root canal treatment in pulp necrosis cases. When pulp vitality is not compromised there is an increase in the number of endodontists who choose single visit root canal treatment.